2020
DOI: 10.4103/jpn.jpn_107_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sedative effect of dexmedetomidine versus midazolam for sedation of children while undergoing computerized tomography imaging

Abstract: A BSTRACT Background: Pediatric anxiety and restlessness may create issues and difficulties in performing accurate diagnostic studies even noninvasive ones, such as radiological imaging. There are some agents that will help to get this goal. This study aimed to compare the intranasal effect of dexmedetomidine (DEX) and midazolam (MID) for sedation parameters of children undergoing computerized tomography (CT) imaging. Materials and Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Two RCTs, 35,41 four cohort studies and other nonrandomized studies, 21,42,44,45 and one case series 52 reported the use of DEX specifically for sedation to facilitate radiologic imaging, generally in children. As above, pooling of efficacy results was not feasible.…”
Section: Sedation To Facilitate Radiologic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two RCTs, 35,41 four cohort studies and other nonrandomized studies, 21,42,44,45 and one case series 52 reported the use of DEX specifically for sedation to facilitate radiologic imaging, generally in children. As above, pooling of efficacy results was not feasible.…”
Section: Sedation To Facilitate Radiologic Imagingmentioning
confidence: 99%
“…Study designs included 11 RCTs, 22,[32][33][34][35][36][37][38][39][40][41] 13 cohort studies and other nonrandomized studies, [19][20][21]23,[42][43][44][45][46][47][48][49][50] and 11 case series and case reports. 12,[51][52][53][54][55][56][57][58][59][60] Six of the included studies were conference abstracts.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Dexmedetomidine is a newer sedative drug that is a selective α 2 agonist and acts as a central agent in the brain and spinal cord [ 13 ]. One of the most important advantages of dexmedetomidine is its low potential for respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…It has little effect on the structure of the upper respiratory tract [ 14 ]. Therefore, dexmedetomidine is preferred over other sedatives in patients at high risk of upper airway obstruction, such as those with a history of obstructive sleep apnea [ 13 , 14 ]. For these reasons, we believe that dexmedetomidine is the safest and most suitable sedative for patients with croup.…”
Section: Discussionmentioning
confidence: 99%
“…Dex is a potent α2-adrenergic agonist, used to induce sedation, reduce the dose of anesthetic agent, and improve hemodynamic stability, which suggests that it can be a suitable adjuvant to ketamine anesthesia. [ 11 ] Propofol is a sedative-hypnotic agent with rapid onset and short duration of action. It has been proposed that propofol can reduce the incidence of emergence agitation.…”
Section: Introductionmentioning
confidence: 99%